Peran Insentif dan Motivasi terhadap Kinerja Karyawan PT. Kb Bank Tbk. - Rosinta Rosinta; Lingga Yuliana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study aims to identify the role of incentives and motivation on employee performance. This study is a qualitative descriptive study. Respondents are employees of PT.Kb Bank Tbk. The data source uses primary data. Primary data was obtained from interviews with employees of PT.Kb Bank Tbk which were conducted in November 2024. The results of the study indicate that there is an influence between incentives and motivation on employee performance at PT.Kb Bank Tbk. The managerial implications in this study are that companies must be adaptive in responding to matters related to incentives and motivation. The need for a draft regulation that can provide achievements in providing other incentives and the need for stimulus so that employees can be motivated to work such as employee gathering activities and certified training can be some options for this.